2017
DOI: 10.1007/s00024-017-1575-1
|View full text |Cite
|
Sign up to set email alerts
|

Near-Fault Broadband Ground Motion Simulations Using Empirical Green’s Functions: Application to the Upper Rhine Graben (France–Germany) Case Study

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The scarcity of strong motion data in metropolitan France meant that this technique was of very limited use in France, as there were few wellcharacterized events available (i.e., in terms of 3D location, magnitude, focal mechanism), and those that were available were clearly associated with a specific fault of interest. In the framework of SINAPS@, the work performed by Del Gaudio et al (2017) that arose through an investigation of the source parameters, concluded on the capacity of such EGF kinematic models to predict strong motion in agreement with the GMPE predictions for the same scenario, including the variability of several intensity parameters. Dujardin et al (2018a) conducted an extensive sensitivity study on a canonical case using the same EGF summation and kinematic source model.…”
Section: Toward Physical Based Strong Motion Predictionmentioning
confidence: 99%
“…The scarcity of strong motion data in metropolitan France meant that this technique was of very limited use in France, as there were few wellcharacterized events available (i.e., in terms of 3D location, magnitude, focal mechanism), and those that were available were clearly associated with a specific fault of interest. In the framework of SINAPS@, the work performed by Del Gaudio et al (2017) that arose through an investigation of the source parameters, concluded on the capacity of such EGF kinematic models to predict strong motion in agreement with the GMPE predictions for the same scenario, including the variability of several intensity parameters. Dujardin et al (2018a) conducted an extensive sensitivity study on a canonical case using the same EGF summation and kinematic source model.…”
Section: Toward Physical Based Strong Motion Predictionmentioning
confidence: 99%
“…An additional study (Del Gaudio et al, 2016) is modelling ground motion in the Upper Rhine Graben with the help of the empirical green function approach (Del Gaudio et al, 2015). It is hoped that these studies will provide new insights for reducing epistemic uncertainty in faultbased PSHA of the Upper Rhine Graben.…”
Section: Perspectivesmentioning
confidence: 99%
“…Del Gaudio et al (2017) evaluate near-source ground motion variability of real earthquakes from simulated broadband ground motion based on kinematic source models and empirical Green's functions (EGF).…”
Section: Section Iii: Kinematic Rupture Modelingmentioning
confidence: 99%